ASOSIASI JENIS BURUNG PADA KAWASAN HUTAN MANGROVE DI ANJUNGAN KOTA PALU - Abdul Gafur; Elhayat Labiro; Moh. Ihsan (Jurnal Warta Rimba, 2016)
Mangrove is a forest located in coastal area which always or regularly inundated by sea water and affected by the tide but unaffected by the climatic.  The condition of archipelago in Indonesia led to a diverse ecosystem.  In turn the diverse of this ecosystem creates a high diversity of flora and fauna.  Birds are wild animals living in the world and have an important role in preserving the environment, example as a pest controller, a seed disperser and pollinator. Mangrove area in pavilion of Palu city specifically is not known yet about birds’ relationship or dependences on Mangrove in pavilion of Palu city.  The purpose of this research is to know the association of birds and Mangrove around pavilion of Palu city.  This research was conducted for 2 months which started on June-August 2015.  This research used Concentration Counts method with 4 points spread on Mangrove area in pavilion of Palu city.  The observation was made at 05.30 am–07.30 am WITA or at 04.00 pm–06.00 pm WITA.  There were 10 families and 15 species of birds in this research.  The species of birds associated with point X (6.7) were 11 species, X (10.0) were 4 species and X (30.0) were 12 species.   The species of birds that have high association number was the yellow-vented bulbul (Pycnonotus goiavier), associated with the pasific swallow (Hirundo Tahitica) and firm associated with the gould’s bronze cuckoo (Chrysococcyx russatus), White-Breasted Waterhen (Amaurornis Phoenicurus), White-Shouldered Triller (Lalage sueurii), lemon-bellied white-eye (Zosterops Chloris) and the zitting cisticola (Cisticola Juncidis).Keywords: Diversity, Association, Bird, Mangrove